RESEARCH OF HEAT TREATMENT OF CEMENT USED IN CONSTRUCTION OF BRIDGE TRANSITION THROUGH KERCHEN STRAIT - A. R. Solovyanchik; S. M. Pulyaev; I. S. Pulyaev (Вестник СибАДИ, 2018)
Introduction. The article discusses the cements’ heat generation issues used in the construction of the bridge across the Kerch Strait. This question is important because of the construction in dry hot climate’s conditions.Materials and methods. The research is conducted with the use of modern information and analytical systems, which allow to obtain the results closing to real conditions. Therefore, the research results of the cement type influence on the dissipation rate and the nature changes of its integral isothermal heat dissipation are shown in the article. The modern design complex repeatedly tested in practice while carrying out thermal calculations of concrete hardening on different massive objects is applied for the research.Results. As a result, the recommendations by the cements of various types’ usage in construction of the Kerch bridge and other similar extra-curricular facilities, which are included in the basis of the developed technological regulations for the production of preparatory, reinforcement, formwork and concrete year-round construction, are presented. The article would be interesting and useful for engineering specialists, who work in real construction conditions, and for experts, who deal with the problem of high consumer concrete properties’ ensuring.